The Precise Structures and Stereochemistry of Trihydroxy-linoleates Esterified in Human and Porcine Epidermis and Their Significance in Skin Barrier Function: IMPLICATION OF AN EPOXIDE HYDROLASE IN THE TRANSFORMATIONS OF LINOLEATE - Chiba, Takahito (J Biol Chem, 2016)
Creation of an intact skin water barrier, a prerequisite for life on dry land, requires the lipoxygenase-catalyzed oxidation of the essential fatty acid linoleate, which is esterified to the ω-hydroxyl of an epidermis-specific ceramide. Oxidation of the linoleate moiety by lipoxygenases is proposed to facilitate enzymatic cleavage of the ester bond, releasing free ω-hydroxyceramide for covalent binding to protein, thus forming the corneocyte lipid envelope, a key component of the epidermal barrier. Herein, we report the transformations of esterified linoleate proceed beyond the initial steps of oxidation and epoxyalcohol synthesis catalyzed by the consecutive actions of 12R-LOX and epidermal LOX3. The major end product in human and porcine epidermis is a trihydroxy derivative, formed with a specificity that implicates participation of an epoxide hydrolase in converting epoxyalcohol to triol. Of the 16 possible triols arising from hydrolysis of 9,10-epoxy-13-hydroxy-octadecenoates, using LC-MS and chiral analyses, we identify and quantify specifically 9R,10S,13R-trihydroxy-11E-octadecenoate as the single major triol esterified in porcine epidermis and the same isomer with lesser amounts of its 10R diastereomer in human epidermis. The 9R,10S,13R-triol is formed by S(N)2 hydrolysis of the 9R,10R-epoxy-13R-hydroxy-octadecenoate product of the LOX enzymes, a reaction specificity characteristic of epoxide hydrolase. The high polarity of triol over the primary linoleate products enhances the concept that the oxidations disrupt corneocyte membrane lipids, promoting release of free ω-hydroxyceramide for covalent binding to protein and sealing of the waterproof barrier.